Pengembangan Sistem Informasi Barang Hilang Markas Komando Keamanan Universitas Brawijaya berbasis Progressive Web App - Nofath Zukhrufi Haideal; Agi Putra Kharisma; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Losing goods such as being negligent in guarding goods can result in the emergence of a criminal act, namely embezzlement of goods. Embezzlement of goods is a case that the goods from the owner are already in the hands of the perpetrator without the perpetrator committing a crime. Based on criminal statistics for 2021, there were 37,097 crimes related to fraud, embezzlement, and corruption in 2020. The researcher also got direct information from UB Security who said that cases of lost goods are not uncommon in UB's campus environment. In addition, information dissemination of missing items has not been implemented in UB. Therefore, we need a solution in the form of a system that can provide information about the incident of lost goods. The development of the PWA Lost and Found UB website uses the Prototyping development method using several tests, namely validation testing using Black-box Testing, usability testing (effectiveness) using Scenario Testing, and usability testing (satisfaction) using the System Usability Scale (SUS). The test results show that the functional requirements run well and users can perform all testing scenarios properly and have an effectiveness level of 100% for each user. The SUS score obtained was 83 which illustrates several points in SUS, namely the Grade Scale with a value of B, an Adjective Rating with an Excellent value, and the Acceptability Range with an Acceptable value.